Analysis On The Utilization Of Village Funds In Cash For Work Program In Bulukumba Regency, South Sulawesi Indonesia - Umar Nain, Andi Agustang, Jumadi.S (International Journal of Advanced Science and Technology, 2020)
This study aims to analyze the utilization of Village Funds in cash for work program in Villages. The program is interesting to be analyzed because it is claimed by the government as the empowerment of marginal community involved in the development of infrastructure in Villages. This study used qualitative approach with descriptive analysis. Then selected 3 villages, namely Kambuno, ara and Bulolohe Village as the locus of research because the three villages have complexity of problems in the implementation of cash for work in Bulukumba Regency. The selection of informants used purposive sampling technique. The total amount of informants in every village selected 6 people, from the head of village, activities executor and representativeness of society from the head of builder, construction worker and unemployed residents in the village. Data collection was done by observation, interview and documentation techniques. Data analysis was done through 3 stages, namely data reduction, data presentation and verification and conclusion. The results showed that the utilization of village funds in cash for work programs in the village was not yet fully an activity of community empowerment, because it only involved labor in the village at the implementation stage. Efforts have not been made to increase the capacity of the community to live independently, thus when infrastructure development is complete they have the potential to become unemployed again. In addition, the stipulation of 30% of work wages evenly and uniformly in every infrastructure development in the village has implications for community self-reliance. The implication is to reduce community participation because they want to be involved in village development, especially infrastructure development, if they are given maximum wages.